The effect of chloramphenicol on ascorbic acid contents of Lamellidens corrianus (lea) and Parreysia cylindrica (Annandale and Prashad). - Nandurkar, H P; Zambare, S P (Journal of Ecobiotechnology, 2012)
Lethal and sublethal exposure of chloramphenicol, one of the broad spectrum antibiotics, changed the ascorbic acid level in various tissues of the freshwater bivalves, L. corrianus and P. cylindrica. The acute dose of chloramphenicol (LC50/2) 470.37PPM was given to L. corrianus and 369.09PPM to P. cylindrica up to 96 hours. The chronic (LC50/10) concentrations used were 94.07 PPM and 73.81 PPM for L. corrianus and P. cylindrica respectively. up to 21 days. The ascorbic acid contents were estimated in mantle, gill, foot, testis, ovary, whole body and digestive gland after 24 and 96 hours of acute and 7, 14 and 21 days of chronic exposure.The level of ascorbic acid showed decrease in gill and whole body exposed to chloramphenicol in L. corrianus. The maximum decrease was observed in foot of L. corrianus while in P. cylindrica there was increase in ascorbic acid contents after chronic exposure of chloramphenicol. The maximum ascorbic acid content was observed in mantle and lowest in digestive gland. In P. cylindrica maximum decrease was showed by digestive gland after chronic exposure of chloramphenicol.